(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
Training has occupied a leading position in a large number of developed and developing countries alike in order to develop the skills of workers in line with the changes and developments of the era, including monitoring compliance in banks, which is one of the most important jobs in banking work to trailing and monitor the bank’s compliance with laws, regulations and instructions in order to achieve its goals Therefore, the problem of this research focuses on the following question: What is the role of training in enhancing banking compliance at the present time? In order to clarify the relationship between the main and sub-research variables, two main hypotheses and three sub-hypotheses were formulated for each hypothesis, and the questionnaire was adopted as a tool in collecting data and information related to the research, which was distributed to the employees of the Banking Compliance Supervision Department in banks, the research sample of (12) banks, two governmental and ten Private banks, using the descriptive and analytical approach, as well as the use of the simple linear correlation coefficient and the simple linear regression analysis to test the research hypotheses. The statistical analyzes have produced a number of results, perhaps the most prominent of which is the presence of a statistically significant relationship between the training and procedures of the Banking Compliance Monitor and the presence of a statistically significant effect between the training and procedures of the Banking Compliance Monitor, Which requires banks to provide scientific resources to compliance auditors to increase their banking and legal expertise, enhance analytical skills, and familiarity with regulations, legislation, and professional and ethical oversight requirements.